Imprinting of the MEDEA polycomb gene in the Arabidopsis endosperm. - Kinoshita, T (1999)
In flowering plants, two cells are fertilized in the haploid female gametophyte. Egg and sperm nuclei fuse to form the embryo. A second sperm nucleus fuses with the central cell nucleus that replicates to generate the endosperm, which is a tissue that supports embryo development. MEDEA (MEA) encodes an Arabidopsis SET domain Polycomb protein. Inheritance of a maternal loss-of-function mea allele results in embryo abortion and prolonged endosperm production, irrespective of the genotype of the paternal allele. Thus, only the maternal wild-type MEA allele is required for proper embryo and endosperm development. To understand the molecular mechanism responsible for the parent-of-origin effects of mea mutations on seed development, we compared the expression of maternal and paternal MEA alleles in the progeny of crosses between two Arabidopsis ecotypes. Only the maternal MEA mRNA was detected in the endosperm from seeds at the torpedo stage and later. By contrast, expression of both maternal and paternal MEA alleles was observed in the embryo from seeds at the torpedo stage and later, in seedling, leaf, stem, and root. Thus, MEA is an imprinted gene that displays parent-of-origin-dependent monoallelic expression specifically in the endosperm. These results suggest that the embryo abortion observed in mutant mea seeds is due, at least in part, to a defect in endosperm function. Silencing of the paternal MEA allele in the endosperm and the phenotype of mutant mea seeds supports the parental conflict theory for the evolution of imprinting in plants and mammals.